Ecological patterns in the skin microbiota of frogs from tropical Australia. Issue 21 (27th September 2018) - Christian, Keith; Weitzman, Chava; Rose, Alea; Kaestli, Mirjam; Gibb, Karen
Abstract: The microbiota of frog skin can play an important role in protecting against diseases and parasites. The frog skin microbial community represents a complex mix of microbes that are promoted by the chemical environment of the frog skin and influenced by the animal's immediate past environment. The microbial communities of six species of frogs sampled from the campus of Charles Darwin University (CDU) were more similar within species than between species. The microbiota of the introduced cane toad ( Rhinella marina ) was most dissimilar among the species. Pairwise comparisons showed that the microbial communities of each species were different, except for the terrestrial Litoria nasuta and the arboreal L. rothii . The microbial communities of the six species were not related to ecological habit (arboreal or terrestrial), and neither was the alpha diversity of the microbes. The core microbes (defined as being on ≥90% of individuals of a species or group) were significantly different among all species, although 89 microbial operational taxonomic units (OTUs) were core microbes for all six species at CDU. Two species, Rhinella marina and Litoria rothii, were sampled at additional sites approximately 10 and 30 km from CDU. The microbial communities and the core OTU composition were different among the sites, but there were nevertheless 194 ( R. marina ) and 181 ( L .  rothii ) core OTUs present at all three sites. Thus, the core microbiota varied with respect to geographic range and sample size. Abstract : The skin microbiota of six frog species was studied at one site, and there were substantial species‐specific differences despite there being very close geographic associations among the species. Two species were sampled at additional sites 10 and 30 km from the first site, and this information was used to evaluate the utility of the concept of a core microbiota.